MEMBANGUN JARINGAN VIRTUAL PRIVATE NETWORK (VPN) DENGAN METODE TUNNELING MENGGUNAKAN UBUNTU 11.10 PADA LABORATORIUM JARINGAN STMIK PPKIA PRADNYA PARAMITA MALANG - Muhsyi, Abdul; Wahyuningsih, Dian (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2014)
Local computer network is a computer network that is built on the college STMIK PPKIA Pradnya Paramita Malang and serves as a support learning tool for students. This private network built and designed by an Admin. Admin should always monitor network construction. In order for the construction of the network remains stable. But not forever a network admin will continue to be on a server computer, there are times when an Admin has a personal interest that requires Admin leave his job. It takes a special application that can to remote computers with a remote server.Virtual Private Network or VPN is better known by the tunneling method is implemented on a local network to develop local networks that exist in universities, facilitate an Admin to connect to servers and computers to remote computers with a remote server.VPN has been tested on a local network STMIK PPKIA Pradnya Paramita Malang Ubuntu11.10 operating system. The result of this research is the establishment of a network virtual private network (VPN) with tunneling method in laboratory network Ubuntu11.10 STMIK PPKIA Pradnya Paramita Malang.Â Keywords: local network, VPN, Server, Client